Mo2N / Fe3Mo3N-NC electrocatalyst and zinc-air battery application

By using Mo2N/Fe3Mo3N-NC electrocatalyst in zinc-air batteries, the problem of slow ORR and OER kinetic processes in zinc-air batteries is solved, and excellent dual-functional activity and high power density are achieved, which improves the overall zinc-air battery. performance.

CN119400879APending Publication Date: 2025-02-07CHINA THREE GORGES UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411326243.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The kinetic processes of oxygen reduction reaction (ORR) and oxygen precipitation reaction (OER) in existing zinc-vac batteries are slow and the thermodynamic energy barrier is high, which limits the overall conversion efficiency of zinc-vac batteries. Traditional precious metal catalysts are difficult to achieve large-scale application due to their scarcity, expensiveness, poor stability and insufficient bifunctionality.

Method used

Mo2N/Fe3Mo3N-NC electrocatalyst is used, which is prepared by introducing pyrrole as a secondary nitrogen source and coating metal ions in a nitrogen-doped carbon support to form a cube ZIF-8-derived NC frame, which is prepared by high temperature pyrolysis.

Benefits of technology

The dual-functional activity of ORR and OER in zinc-empty batteries was achieved, with the oxygen reduction half-wave potential of 0.88-0.89 V vs. RHE and the oxygen evolution overpotential was 290-320 mV, which improved the power density and charge and discharge cycle stability of zinc-empty batteries. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400879A_ABST
    Figure CN119400879A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a nitride-loaded nitrogen-doped carbon electrocatalyst (Mo2N / Fe3Mo3N-NC) and application of the nitride-loaded nitrogen-doped carbon electrocatalyst to a zinc-air battery. The ZIF-8 precursor is subjected to pyrolysis, and NC powder is obtained; the preparation method comprises the following steps: sequentially adding meso-tetra (4-carboxyphenyl) porphin, ferric chloride hexahydrate, nickel nitrate hexahydrate and phosphomolybdic acid into water, and stirring until the materials are dissolved to obtain a mixed solution; and adding NC powder into a pyrrole dispersion solution, performing ultrasonic dispersion, adding the mixed solution, uniformly stirring, centrifuging, drying, and performing high-temperature pyrolysis to obtain the Mo2N / Fe3Mo3N-NC electrocatalyst. The catalyst has excellent ORR / OER bifunctional activity, and as an air cathode of a zinc-air battery, high power density and excellent charge-discharge cycle stability are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a class of highly efficient and inexpensive cathode electrocatalysts for zinc-air batteries, and in particular to a novel Mo 2 N / Fe 3 Mo 3 Preparation method of N-NC electrocatalyst and its application in zinc-air batteries. Background Art

[0002] With the continuous development of new energy technologies, zinc-air batteries, as an ideal energy conversion and storage device, have an increasingly broad application prospect. In the future, it is necessary to continuously strengthen technology research and development and industrialization investment, improve energy conversion efficiency, reduce costs, improve stability, and expand application fields to achieve breakthrough progress in order to realize the large-scale application of zinc-air batteries. Oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are the key links in realizing energy conversion and storage in zinc-air batteries, but due to the slow kinetic process and high thermodynamic energy barrier, the overall conversion efficiency of zinc-air batteries is severely limited. Although traditional precious metal catalysts (such as Pt, Ru and Ir) have excellent performance in improving oxygen electrocatalytic activity, their scarcity, high cost, poor stability and lack of bifunctionality limit their feasibility in large-scale applications. Based on this background, research has turned to non-precious metal catalysts that are abundant in resources, low-cost, and have excellent bifunctional activity and stability.

[0003] Transition metal nitrides (TMNs) are used as electrocatalysts due to their stable structure and good conductivity. On the one hand, TMNs, as an interstitial nanocrystalline material, have covalent, ionic and metallic bond characteristics; on the other hand, due to the doping of N, the metal lattice will expand, the metal spacing will increase, and the interaction force between metal atoms will weaken, resulting in the corresponding d-band contraction and an increase in the density of states near the Fermi level, thereby enhancing its conductivity. However, in the current reported literature, the synthesized TMNs are large in size (50 nm~200 nm) and have limited exposed active sites, which limits their electrocatalytic activity. Therefore, nitrogen-doped carbon-loaded TMNs materials with high porosity have been widely studied. Among them, molybdenum nitride (MoN) 2 N) nitrogen-doped carbon materials have good OER catalytic activity, but poor ORR activity. Therefore, it is necessary to introduce species with good ORR activity to improve their bifunctional activity and apply them to zinc-air battery devices. Based on the above background, this patent uses cubic ZIF-8-derived NC as a framework, wraps polypyrrole and meso-tetra(4-carboxyphenyl)porphine, and introduces a metal source at the same time. After annealing, Mo is formed. 2 N / Fe 3 Mo 3N-NC electrocatalyst. This electrocatalyst has excellent bifunctional activity. When assembled as the air cathode of a zinc-air battery, it achieves high power density and excellent charge-discharge cycle stability, and has potential application value in the field of zinc-air batteries.

[0004] Purpose of the Invention The purpose of the present invention is to provide a zinc-air battery air cathode electrocatalyst Mo with excellent dual functions 2 N / Fe 3 Mo 3 N-NC. The specific steps of its preparation method are: Step 1: Pyrolyze the ZIF-8 precursor to obtain NC powder; Step 2: adding meso-tetrakis(4-carboxyphenyl)porphine, ferric chloride hexahydrate, nickel nitrate hexahydrate, and phosphomolybdic acid to water in sequence, stirring until dissolved to obtain a mixed solution; Step 3: Add NC powder to the pyrrole dispersion solution, add the above mixed solution after ultrasonic dispersion, stir evenly, centrifuge, dry, and pyrolyze at high temperature to obtain Mo 2 N / Fe 3 Mo 3 N-NC electrocatalysts.

[0005] The ZIF-8 precursor in the present invention is obtained by uniformly mixing a dimethyl imidazole solution and a zinc nitrate solution in a surfactant, hexadecyl trimethyl ammonium bromide.

[0006] In step 2, the mass ratio of meso-tetrakis(4-carboxyphenyl)porphine, ferric chloride hexahydrate, nickel nitrate hexahydrate, and phosphomolybdic acid is 5:5:1:5-5:30:1:7.5.

[0007] In step 3, the mass ratio of pyrrole and NC powder added is 24:25.

[0008] The technical solution of the present invention further improves the catalytic performance by introducing pyrrole as a secondary nitrogen source and encapsulating metal ions in a nitrogen-doped carbon carrier.

[0009] In step 3, the high temperature pyrolysis temperature is 900-1000° C. under an inert atmosphere to obtain the product.

[0010] Mo 2 N / Fe 3 Mo 3 The N-NC electrocatalyst has peaks at about 26°, 32°, 35°, 37°, 40°, 42°, 43°, and 46° in the XRD diffraction spectrum, and also has peaks at about 63° and 76°.

[0011] A zinc-air battery cathode electrocatalyst, the catalyst is the Mo 2 N / Fe 3 Mo 3 N-NC electrocatalysts.

[0012] A zinc-air battery, comprising the Mo 2 N / Fe 3 Mo 3 N-NC electrocatalyst. The zinc-air battery includes quasi-solid-state and liquid-state batteries.

[0013] An ORR and OER bifunctional catalyst, comprising the Mo 2 N / Fe 3 Mo 3 N-NC electrocatalysts.

[0014] Based on the rich nitrogen content and multi-component active sites in the catalyst, including Mo 2 N, Fe 3 Mo 3 N, Ni species, Mo 2 N / Fe 3 Mo 3 N-NCs exhibit excellent ORR and OER bifunctional activities.

[0015] The Mo involved in the present invention 2 N / Fe 3 Mo 3 N-NC electrocatalyst and preparation method have the following significant features: (1) Excellent ORR / OER bifunctional activity, with an oxygen reduction half-wave potential of 0.88-0.89 V vs. RHE and an oxygen evolution overpotential (10 mA cm -2 ) is 290-320 mV; (2) As the air cathode of zinc-air batteries, it has achieved high power density (the power density of quasi-solid-state batteries can reach 500 mWcm -2 The power density of liquid batteries can reach 200 mW cm -2 Above), excellent charge and discharge cycle stability (quasi-solid-state battery at 2 mA cm -2 The liquid battery can stably cycle charge and discharge for more than 40 h at a constant current density of 10 mA cm -2 It can stably cycle charge and discharge for more than 900 h at a constant current density). BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 XRD pattern of the sample prepared in Example 1.

[0017] Figure 2SEM image of the sample prepared in Example 1.

[0018] Figure 3 Examples 1, 2, 3, 4 with Pt / C and RuO 2 LSV curves of oxygen reduction reaction and oxygen evolution reaction of the prepared samples.

[0019] Figure 4 Chronoamperometric curve of oxygen reduction reaction between the sample prepared in Example 1 and Pt / C.

[0020] Figure 5 The sample prepared in Example 1 and Pt / C+RuO 2 Discharge curves and power density curves of assembled quasi-solid-state batteries and liquid batteries.

[0021] Figure 6 The sample prepared in Example 1 was used as the air cathode of a quasi-solid-state battery at a current density of 2 mA cm -2 Constant current cycle charge and discharge curve.

[0022] Figure 7 The sample prepared in Example 1 and Pt / C+RuO 2 As the air cathode of liquid battery, at a current density of 10 mAcm -2 Constant current cycle charge and discharge curve.

[0023] Figure 8 XRD patterns of samples of Examples 5, 6, 7, 8 and 9.

[0024] Fig. 9 LSV diagrams of oxygen reduction reaction and oxygen evolution reaction of samples of Examples 5, 6, 7, 8, and 9. DETAILED DESCRIPTION

[0025] Example 1 Step 1: Take 136 ml ultrapure water from beaker A, add 10 g dimethylimidazole, and stir until dissolved; take 24 ml ultrapure water from beaker B, add 0.64 g zinc nitrate hexahydrate, and stir until dissolved; take 4 ml ultrapure water from beaker C, add 14.5 mg hexadecyltrimethylammonium bromide, and stir until dissolved. Pour the solution in beaker C into beaker B, stir evenly at room temperature, and then pour it into beaker A, stir at room temperature for 2 h, then stand for 2 h, centrifuge and wash with methanol, and dry to obtain the ZIF-8 precursor. Then, ZIF-8 was heated to 900°C at 5°C / min in a high-purity Ar atmosphere, and pyrolyzed at high temperature for 2 h to obtain NC powder.

[0026] Step 2: Take 10 ml ultrapure water, disperse 0.1 ml pyrrole, add 100 mg NC powder, and ultrasonicate until uniformly dispersed; take 10 ml ultrapure water, add 10 mg of medium-tetrakis (4-carboxyphenyl) porphine, 60 mg of ferric chloride hexahydrate, 2 mg of nickel nitrate hexahydrate, and 10 mg of phosphomolybdic acid to ultrapure water in turn, and mix evenly; mix the above two solutions, stir at room temperature for 15 min, centrifuge the precipitate, and dry to obtain a black powder. Finally, place the powder in the center of a tube furnace, heat it to 900 ° C at 5 ° C / min in a high-purity Ar atmosphere, and pyrolyze it at high temperature for 2 h to obtain Mo 2 N / Fe 3 Mo 3 N-NC electrocatalyst, labeled as Example 1 sample.

[0027] Figure 1 Example 1 is the XRD spectrum of the catalyst prepared in this example. There are (002) and (101) diffraction peaks of graphitized carbon at around 26° and 43°, which are beneficial to improving conductivity and loading active sites; other sharp diffraction peaks correspond to Mo 2 N (PDF#25-1366) and Fe 3 Mo 3 N (PDF#48-1408), indicating that the sample in Example 1 is a nitride (Mo 2 N / Fe 3 Mo 3 The obtained samples were tested by scanning electron microscopy (SEM). Figure 2 a 2b), it can be seen that most of the sample is well dispersed and uniformly sized cubes, and the cube size is about 150 nm. A small number of cubes are slightly broken and agglomerated together. The sample of this example is prepared into a slurry and dropped onto a rotating disk electrode. 2 The ORR performance was tested in a saturated 0.1 M KOH solution. Figure 3 The ORR LSV curve of case 1 in a is shown in the figure. It can be seen that at 1600 rpm, its half-wave potential is 0.89 V vs. RHE and the limiting current density is 6.3 mA cm -2 , showing excellent ORR performance. Its OER performance was tested in 1 M KOH solution. Figure 3 Example 1 in b is its OER LSV curve. It can be seen from the figure that at 10 mAcm -2 Its potential is 1.53 V vs. RHE at the current density, and the overpotential is 300 mV, which is close to RuO 2 (at 10 mA cm -2The potential at the current density is 1.51 V and the overpotential is 280 mV, showing excellent OER performance. Figure 4 The chronoamperometric curves of the oxygen reduction reaction of the sample of Example 1 and Pt / C tested at a constant voltage of 0.45 V. After 2 h, the current retention rate of Example 1 was 92%, while the current retention rate of Pt / C was 84%, and the stability was better than that of Pt / C. After 5.5 h, the current retention rate of the sample of Example 1 was still 85.6%, indicating its excellent stability. Figure 5 The discharge curve and power density curve of the quasi-solid-state and liquid-state batteries assembled from the samples of Example 1. The power density of the quasi-solid-state battery is as high as 500 mW cm -2 , the power density of liquid batteries can reach 220 mW cm -2 In comparison, Pt / C+RuO 2 The power density of the quasi-solid-state battery is 192 mW cm -2 , the power density of liquid batteries is 142 mW cm -2 , indicating that the sample of Example 1 has excellent performance as the air cathode of zinc-air battery. Figure 6 The quasi-solid-state battery assembled for the sample of Example 1 is 2 mA cm -2 Cyclic charge and discharge curves under constant current density. The battery can be stably charged and discharged for 42 h. The liquid battery assembled from the sample of Example 1 is charged and discharged at 10 mA cm -2 The charge and discharge cycle can be stably maintained at a constant current density for 990 h, while Pt / C+RuO 2 The assembled liquid battery can only be charged and discharged for 250 h ( Figure 7 ), from which it can be concluded that the electrocatalyst of Example 1 has good cycling stability as the cathode of zinc-air batteries.

[0028] Example 2 Step 1: The NC powder preparation process is the same as that in Example 1.

[0029] Step 2: Take 10 ml ultrapure water, disperse 0.1 ml pyrrole, add 100 mg NC powder, and ultrasonicate until uniformly dispersed; take 10 ml ultrapure water, add 10 mg of medium-tetrakis (4-carboxyphenyl) porphine, 10 mg of ferric chloride hexahydrate, 2 mg of nickel nitrate hexahydrate, and 10 mg of phosphomolybdic acid to ultrapure water in sequence, and mix evenly; mix the above two solutions, stir at room temperature for 15 min, centrifuge the precipitate, and dry to obtain a black powder. Finally, place the powder in the center of a tube furnace, heat it to 900 ° C at 5 ° C / min in a high-purity Ar atmosphere, and pyrolyze it at high temperature for 2 h to obtain Mo 2 N / Fe 3 Mo 3 N-NC electrocatalyst, labeled as Example 2 sample.

[0030] The sample was prepared into a slurry and dropped onto a rotating disk electrode. 2 The ORR performance was tested in a saturated 0.1 M KOH solution. Figure 3 The ORR LSV curve of case 2 in a is shown in the figure. It can be seen that at 1600 rpm, its half-wave potential is 0.88 V vs. RHE and the limiting current density is 5.8 mA cm -2 , showing excellent ORR performance. Its OER performance was tested in 1 M KOH solution. Figure 3 Example 2 in b is its OER LSV curve. It can be seen from the figure that at 10 mA cm -2 Its potential at the current density is 1.54 V vs. RHE, and its overpotential is 310 mV, which is not much different from Example 1, showing good OER performance.

[0031] Example 3 Step 1: The NC powder preparation process is the same as that in Example 1.

[0032] Step 2: Take 10 ml ultrapure water, disperse 0.1 ml pyrrole, add 100 mg NC powder, and ultrasonicate until uniformly dispersed; take 10 ml ultrapure water, add 10 mg of medium-tetrakis (4-carboxyphenyl) porphine, 20 mg of ferric chloride hexahydrate, 2 mg of nickel nitrate hexahydrate, and 10 mg of phosphomolybdic acid to ultrapure water in turn, and mix evenly; mix the above two solutions, stir at room temperature for 15 min, centrifuge the precipitate, and dry to obtain a black powder. Finally, place the powder in the center of a tube furnace, heat it to 900 ° C at 5 ° C / min in a high-purity Ar atmosphere, and pyrolyze it at high temperature for 2 h to obtain Mo 2 N / Fe 3 Mo 3 N-NC electrocatalyst, labeled as Example 3 sample.

[0033] The sample was prepared into a slurry and dropped onto a rotating disk electrode. 2 The ORR performance was tested in a saturated 0.1 M KOH solution. Figure 3 The ORR LSV curve of case 3 in a is shown in the figure. It can be seen that at 1600 rpm, its half-wave potential is 0.89 V vs. RHE and the limiting current density is 6.39 mA cm -2 , showing excellent ORR performance. Its OER performance was tested in 1 M KOH solution. Figure 3 Example 3 in b is its OER LSV curve. It can be seen from the figure that at 10 mA cm -2Its potential at the current density is 1.55 V vs. RHE, and its overpotential is 320 mV, which is not much different from Examples 1 and 2, showing relatively excellent OER performance.

[0034] Example 4 Step 1: The NC powder preparation process is the same as that in Example 1.

[0035] Step 2: Take 10 ml ultrapure water, disperse 0.1 ml pyrrole, add 100 mg NC powder, and ultrasonicate until uniformly dispersed; take 10 ml ultrapure water, add 10 mg of medium-tetrakis (4-carboxyphenyl) porphine, 20 mg of ferric chloride hexahydrate, 2 mg of nickel nitrate hexahydrate, and 15 mg of phosphomolybdic acid to ultrapure water in turn, and mix evenly; mix the above two solutions, stir at room temperature for 15 min, centrifuge the precipitate, and dry to obtain a black powder. Finally, place the powder in the center of a tube furnace, heat it to 900 ° C at 5 ° C / min in a high-purity Ar atmosphere, and pyrolyze it at high temperature for 2 h to obtain Mo 2 N / Fe 3 Mo 3 N-NC electrocatalyst, labeled as Example 4 sample.

[0036] The sample was prepared into a slurry and dropped onto a rotating disk electrode. 2 The ORR performance was tested in a saturated 0.1 M KOH solution. Figure 3 The ORR LSV curve of case 4 in a is shown in the figure. It can be seen that at 1600 rpm, its half-wave potential is 0.88 V vs. RHE and the limiting current density is 5.8 mA cm -2 , showing excellent ORR performance. Its OER performance was tested in 1 M KOH solution. Figure 3 Example 4 in b is its OER LSV curve. It can be seen from the figure that at 10 mA cm -2 Its potential is 1.52 V vs. RHE at the current density and the overpotential is 290 mV, showing a more excellent OER performance.

[0037] Compared with Example 1, the experimental steps and the dosage of other drugs are kept unchanged, and nickel nitrate hexahydrate is not added. The XRD pattern of the sample of Example 5 is as follows: Figure 8 As shown, the sample is Mo 2 N-loaded nitrogen-doped carbon electrocatalyst. The ORRLSV curve corresponding to this sample is as follows Fig. 9 As shown in a, it can be seen from the figure that at 1600 rpm, its half-wave potential is 0.9 V vs. RHE and the limiting current density is 6 mA cm -2 , and the ORR performance is excellent. However, the OER performance of this sample is significantly attenuated at 10 mA cm-2 At this current density, its potential increases to 1.57 V vs. RHE, with an overpotential of 340 mV ( Fig. 9 b), indicating its relatively poor ORR / OER bifunctional activity.

[0038] Compared with Example 1, the experimental steps and the dosage of other drugs are kept unchanged, and ferric chloride hexahydrate is not added. The XRD pattern of the sample of Example 6 is as follows: Figure 8 As shown, the sample is still Mo 2 N-loaded nitrogen-doped carbon electrocatalyst. The ORR LSV curve of this sample is shown in Fig. 9 As shown in a, it can be seen from the figure that at 1600 rpm, its half-wave potential drops to 0.84 Vvs. RHE and the limiting current density drops to 5.6 mA cm -2 , its ORR performance is obviously attenuated. The OER LSV curve of this sample is as follows Fig. 9 As shown in b, at 10 mA cm -2 Its potential is 1.55 V vs. RHE at the current density, and the overpotential is 320 mV, which is the same as Example 3. However, due to the attenuation of ORR performance, its ORR / OER bifunctional activity is poor.

[0039] Compared with Example 1, the experimental steps and the amounts of other drugs are kept unchanged, no meso-tetra(4-carboxyphenyl)porphine is added, and the amounts of ferric chloride hexahydrate and nickel nitrate hexahydrate are changed (the amount of ferric chloride hexahydrate is 40 mg, and the amount of nickel nitrate hexahydrate is 4 mg). The XRD of the obtained sample Example 7 is as follows: Figure 8 As shown, the sample of Example 7 is Fe 3 Mo 3 O 8 Particle-supported nitrogen-doped carbon electrocatalyst. The ORR LSV curve of this sample is as follows: Fig. 9 As shown in a, it can be seen from the figure that at 1600 rpm, its half-wave potential drops to 0.84 V vs. RHE and the limiting current density drops to 5.8 mA cm -2 , its ORR performance is obviously attenuated. The OER LSV curve of this sample is as follows Fig. 9 As shown in b, at 10 mA cm -2 Its potential increases to 1.56 V vs. RHE at a high current density with an overpotential of 330 mV, and both ORR and OER performances are poor.

[0040] Compared with Example 1, the experimental steps and the dosage of other drugs are kept unchanged, and phosphomolybdic acid is not added. The XRD pattern of the sample of Example 8 is as follows: Figure 8 As shown, the obtained sample is Fe 3 Mo 3O 8 Particle-supported nitrogen-doped carbon electrocatalyst. The ORR LSV curve of this sample is as follows: Fig. 9 As shown in a, it can be seen from the figure that at 1600 rpm, its half-wave potential drops to 0.87 Vvs. RHE, and the limiting current density is 6.4 mA cm -2 , its ORR performance is attenuated compared with Example 1-4. The OER LSV curve of this sample is as follows Fig. 9 As shown in b, at 10 mA cm -2 Its potential at the current density is 1.54 V vs. RHE, and its overpotential is 310 mV, which is not much different from that of Example 1-4.

[0041] Compared with Example 1, the experimental steps and the dosage of other drugs remain unchanged, and only the amount of nickel nitrate hexahydrate added is changed to 4 mg. The XRD pattern of the sample of Example 9 is as follows: Figure 8 As shown, the sample is Fe 3 O 4 Particle-supported nitrogen-doped carbon electrocatalyst. The ORR LSV curve of this sample is as follows: Fig. 9 As shown in a, it can be seen from the figure that at 1600 rpm, its half-wave potential is 0.89 V vs. RHE and the limiting current density is 6.2 mA cm -2 , and its ORR performance is excellent. The OER LSV curve of this sample is as follows Fig. 9 As shown in b, at 10 mA cm -2 Its potential increased to 1.56 V vs. RHE at the current density, with an overpotential of 330 mV, and its OER performance was attenuated compared with Examples 1-4.

Claims

1. A method for preparing a Mo2N / Fe3Mo3N-NC electrocatalyst, characterized in that: The steps include: Step 1: Pyrolyze the ZIF-8 precursor to obtain NC powder; Step 2: adding meso-tetrakis(4-carboxyphenyl)porphine, ferric chloride hexahydrate, nickel nitrate hexahydrate, and phosphomolybdic acid to water in sequence, stirring until dissolved to obtain a mixed solution; Step 3: Add NC powder to the pyrrole dispersion solution, add the above mixed solution after ultrasonic dispersion, stir evenly, centrifuge, dry, and pyrolyze at high temperature to obtain Mo2N / Fe3Mo3N-NC electrocatalyst.

2. The method for preparing the Mo2N / Fe3Mo3N-NC electrocatalyst according to claim 1, characterized in that: In step 2, the mass ratio of meso-tetrakis(4-carboxyphenyl)porphine, ferric chloride hexahydrate, nickel nitrate hexahydrate, and phosphomolybdic acid is 5:5:1:5-5:30:1:7.

5.

3. The method for preparing the Mo2N / Fe3Mo3N-NC electrocatalyst according to claim 1, characterized in that: In step 3, the mass ratio of pyrrole and NC powder added is 24:

25.

4. The method for preparing the Mo2N / Fe3Mo3N-NC electrocatalyst according to claim 1, characterized in that: In step 3, the high temperature pyrolysis temperature is 900-1000° C. under an inert atmosphere to obtain the product.

5. The Mo2N / Fe3Mo3N-NC electrocatalyst according to any one of claims 1 to 4, characterized in that The Mo2N / Fe3Mo3N-NC electrocatalyst has peaks at approximately 26°, 32°, 35°, 37°, 40°, 42°, 43°, and 46° in the XRD diffraction pattern.

6. A zinc-air battery cathode electrocatalyst, characterized in that The catalyst is the Mo2N / Fe3Mo3N-NC electrocatalyst as described in claim 5.

7. A zinc-air battery, characterized in that: Includes the Mo2N / Fe3Mo3N-NC electrocatalyst as described in claim 5.

8. The zinc-air battery according to claim 7, characterized in that: The zinc-air battery includes quasi-solid-state battery and liquid-state battery.

9. An ORR and OER bifunctional catalyst, characterized in that Includes the Mo2N / Fe3Mo3N-NC electrocatalyst as described in claim 5.